Inhibitor binding mode and allosteric regulation of Na+-glucose symporters. Issue 1 (December 2018) - Bisignano, Paola; Ghezzi, Chiara; Jo, Hyunil; Polizzi, Nicholas F.; Althoff, Thorsten; Kalyanaraman, Chakrapani; Friemann, Rosmarie; Jacobson, Matthew; Wright, Ernest; Grabe, Michael
Abstract Sodium-dependent glucose transporters (SGLTs) exploit sodium gradients to transport sugars across the plasma membrane. Due to their role in renal sugar reabsorption, SGLTs are targets for the treatment of type 2 diabetes. Current therapeutics are phlorizin derivatives that contain a sugar moiety bound to an aromatic aglycon tail. Here, we develop structural models of human SGLT1/2 in complex with inhibitors by combining computational and functional studies. Inhibitors bind with the sugar moiety in the sugar pocket and the aglycon tail in the extracellular vestibule. The binding poses corroborate mutagenesis studies and suggest a partial closure of the outer gate upon binding. The models also reveal a putative Na+ binding site in hSGLT1 whose disruption reduces the transport stoichiometry to the value observed in hSGLT2 and increases inhibition by aglycon tails. Our work demonstrates that subtype selectivity arises from Na+ -regulated outer gate closure and a variable region in extracellular loop EL5. Sodium-dependent glucose transporters (SGLTs) transport sugars across the plasma membrane and play important roles in renal sugar reabsorption. Here authors develop structural models of human SGLT1/2 (hSGLT1/2) in complex with inhibitors which helps to understand inhibitor subtype selectivity.